2021
DOI: 10.5194/bg-18-1049-2021
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of biogenic polyunsaturated aldehydes on metabolism and community composition of particle-attached bacteria in coastal hypoxia

Abstract: Abstract. Eutrophication-driven coastal hypoxia has been of great interest for decades, though its mechanisms remain not fully understood. Here, we showed elevated concentrations of particulate and dissolved polyunsaturated aldehydes (PUAs) associated with the hypoxic waters in the bottom layer of a salt-wedge estuary. Bacterial respiration within the hypoxic waters was mainly contributed by particle-attached bacteria (PAB) (> 0.8 µm), with free-living bacteria (0.2–0.8 µm) only accounting for 25 %–30 % of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Moreover, particle resuspension can indirectly affect dissolved oxygen processes by changing biogeochemical cycles, such as the rate of photosynthesis and nitrification (Gloor et al, 1994;Lou et al, 2000;Valipour et al, 2017). Recently, oxygen consumption within hypoxic waters was found to be mainly generated by particle-attached bacteria in the Pearl River Estuary (Wu et al, 2021). Nevertheless, the impact of particle resuspension on the hypoxic degree and the DO budget has not yet been straightforward to identify.…”
mentioning
confidence: 99%
“…Moreover, particle resuspension can indirectly affect dissolved oxygen processes by changing biogeochemical cycles, such as the rate of photosynthesis and nitrification (Gloor et al, 1994;Lou et al, 2000;Valipour et al, 2017). Recently, oxygen consumption within hypoxic waters was found to be mainly generated by particle-attached bacteria in the Pearl River Estuary (Wu et al, 2021). Nevertheless, the impact of particle resuspension on the hypoxic degree and the DO budget has not yet been straightforward to identify.…”
mentioning
confidence: 99%
“…These are good candidates for future amendment experiments as we know little about their function in marine diatom ecosystems. As mentioned above, amendment experiments showed that some organisms are stimulated by oxylipins, like the bacterial epibionts of diatoms [14] and particle-associated communities [15,56], but most organisms are inhibited in some way by PUAs, including free-living bacteria and particle-associated communities at higher concentration exposures [5,13,14,19,57].…”
Section: Novel Oxylipinsmentioning
confidence: 84%
“…Very recently, Eastabrook et al have suggested that PUA is not the main driver of diatom-bacteria interactions in laboratory cultures [25]. Recent publications also consider the significant role of attached bacteria in phosphorus recycling in nature [26,27].…”
Section: Introductionmentioning
confidence: 99%